Criminal Penalties For Asset Confiscation In Corruption Cases: A Due Process Model Perspective - Gatra Setya El Yanda; Yuliati; Fachrizal Affandi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
Corruption is an extraordinary crime that causes state financial losses and hinders national development. Therefore, its handling is not sufficient only through the main punishment of imprisonment and fines, but also through the recovery of state assets. This study aims to analyze the construction of the criminal confiscation penalty as a substitute for state losses in corruption cases in Indonesia and the mechanism for imposing additional penalties of confiscation of assets based on the due process model. The research method used is normative juridical legal research with a statutory approach, a conceptual approach, and a case approach. Primary legal materials in the form of laws and regulations, court decisions, and secondary legal materials in the form of literature and scientific journals were analyzed qualitatively. The results of the study indicate that the criminal confiscation penalty is an additional penalty that has a strategic function to eliminate profits from crime, recover state losses, and provide a deterrent effect to perpetrators of corruption. The legal basis is found in the Corruption Eradication Law which allows for the confiscation of assets from corruption and other assets belonging to convicts to pay compensation. The mechanism for imposing additional penalties of asset confiscation must be implemented through the stages of investigation, prosecution, trial examination, judge's decision, and execution in a legal, proportional, and accountable manner. The due process model approach demands protection of the rights of the accused and third parties acting in good faith, so that asset confiscation is not carried out arbitrarily. Therefore, additional penalties of asset confiscation become an effective instrument in eradicating corruption when implemented based on the principles of legality, justice, proportionality, and legal certainty.